2011
DOI: 10.1177/0194599811411878
|View full text |Cite
|
Sign up to set email alerts
|

False‐Negative Sentinel Lymph Node Biopsy in Head and Neck Melanoma

Abstract: False-negative SLNB is more likely to occur when a single sentinel lymph node is harvested. There is significant treatment delay in patients with false-negative SLNB. False-negative SLNB is associated with poor outcome in patients with melanoma of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 36 publications
4
29
0
2
Order By: Relevance
“…One of our five patients with progression had a nodal recurrence in the previously negative SLN area which led to a false-negative rate of 16.7%. Several investigations have found false-negative SLN rates in melanoma patients in the range 0.6-32.1% [33][34][35][36][37]. The highest false-negative rates have been reported for head and neck melanomas [33], which is in the line with our investigation in which there was one patient who had a false-negative SLN in the submandibular region.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One of our five patients with progression had a nodal recurrence in the previously negative SLN area which led to a false-negative rate of 16.7%. Several investigations have found false-negative SLN rates in melanoma patients in the range 0.6-32.1% [33][34][35][36][37]. The highest false-negative rates have been reported for head and neck melanomas [33], which is in the line with our investigation in which there was one patient who had a false-negative SLN in the submandibular region.…”
Section: Discussionsupporting
confidence: 90%
“…Several investigations have found false-negative SLN rates in melanoma patients in the range 0.6-32.1% [33][34][35][36][37]. The highest false-negative rates have been reported for head and neck melanomas [33], which is in the line with our investigation in which there was one patient who had a false-negative SLN in the submandibular region. Gadd et al also reported more difficulties in primary melanomas located in the head and neck region due to the close proximity of the primary injection site and the potential SLN, and also due to technical expertise required because of the important vascular and nervous structures in this area [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In patients with cutaneous melanoma, SLN false-negative rates in the range 0.6-32.1 % have been reported [33,34]. Our study patient suffered from an acral lentiginous melanoma on the right foot with a thickness of 5.00 mm and a history of two excised negative SLNs in the right groin.…”
Section: Discussionmentioning
confidence: 82%
“…Our study patient suffered from an acral lentiginous melanoma on the right foot with a thickness of 5.00 mm and a history of two excised negative SLNs in the right groin. High falsenegative rates have generally been reported in head and neck melanomas because of the difficulties associated with the close proximity of the primary injection site and the potential SLN, but also because of the technical expertise required for successful biopsy in this area with its complex vascular and nervous structure [33,34]. Additionally, a 1-day protocol of lymphatic mapping is suggested in head and neck melanomas which should lead to a reduction of the false-negative rate [35,36].…”
Section: Discussionmentioning
confidence: 99%